Articulations of Language and Value(s) in Scholarly Publishing Circuits - Shi, Julie (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
This paper examines how the use of and preference for the English language in scholarly communication enacts epistemic oppressions on global, regional, and local stages to delegitimize knowledge and knowers active in other languages and epistemological frameworks. Specifically, this paper argues that internationalized languages of economic and metrics-based value interact and intersect with the over-valuation of English, which has detrimental consequences. Four readings of the interplays between language and value in the scholarly ecosystem are presented. As questions of knowledge production, epistemic oppression, and justice are not confined to one discipline or community, each reading engages with the theory and praxis of scholars from local and Indigenous communities, and scholars and practitioners in a range of other areas. The first reading, Language Has Value, examines the knowledge and value embedded in languages, as well as the implications of monolingualism for global knowledge production and use. Focusing on the publishing industry, Language of Value interrogates the internationalized economic values that shape mainstream approaches to open access and overlook regional situations. Language of Evaluation attends to the symbolic market of research metrics and evaluation criteria that forces researchers to choose between topics that are locally relevant and those deemed important by the mainstream community. These readings are followed, in Language and Value, by lessons learned from established models and tools for knowledge production and dissemination that actively resist intersecting oppressions. The paper closes with a call to the research community to imagine and work for sustainable and equitable approaches to scholarly communication that break open and away from the epistemic enclosures dominating the present system.